To find the specific terms of the sequence defined by the rule \( A(n) = 6 + (n - 1)(3) \), we can substitute \( n \) with 3, 5, and 10 to get the required terms.
-
Finding \( A(3) \): \[ A(3) = 6 + (3 - 1)(3) \] \[ = 6 + (2)(3) \] \[ = 6 + 6 \] \[ = 12 \]
-
Finding \( A(5) \): \[ A(5) = 6 + (5 - 1)(3) \] \[ = 6 + (4)(3) \] \[ = 6 + 12 \] \[ = 18 \]
-
Finding \( A(10) \): \[ A(10) = 6 + (10 - 1)(3) \] \[ = 6 + (9)(3) \] \[ = 6 + 27 \] \[ = 33 \]
The results are:
- \( A(3) = 12 \)
- \( A(5) = 18 \)
- \( A(10) = 33 \)
Thus, the third term is 12, the fifth term is 18, and the tenth term is 33.